The Effect of Video Media With Google Form on Student Learning Results in Learning Solar System in Junior High School - Dita Kharisma Mustikaningrum; Sutarto Sutarto; Agustiningsih Agustiningsih (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Current technological developments have influenced the field of education in both individuals and groups. Technological advances alone can support science thought processes in students. Likewise the teacher, it is recommended to be more innovative in the application of technology in learning science. The purpose of this study is the influence of the use of google form assisted video media on improving junior high school student learning outcomes. This type of research is experimental research with Post-test Only Design design. The selection of samples from 9 classes is done by drawing homogeneity tests. Data analysis techniques used in this study are statistical analysis techniques in the form of normality tests and hypothesis testing (t-test). Based on the results of the t-test analysis conducted where Asymp. Sig. (2-tailed) learning outcomes are 0.027 and Asymp. Sig. (2-tailed) retention of learning outcomes is 0.012 so it produces a value of less than 0.05 where it answers the hypothesis if there is a significant effect on learning outcomes and retention of student learning outcomes in Solar System learning using video forms assisted by Google forms. This study concludes that the Google form-assisted video media has a significant influence on student learning outcomes and retention of student learning outcomes, while also increasing student activity in learning science.